2016
DOI: 10.1021/acs.joc.6b01265
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Ocotillol-Type Ginsenosides

Abstract: A total of 14 ocotillol-type ginsenosides were conveniently synthesized employing glycosylation of ocotillol sapogenin derivatives with glucosyl ortho-alkynylbenzoate donors under the promotion of a gold(I) catalyst as the key step. Relying on a rational protecting group strategy and the unexpected regioselectivity of the glycosylation of the 3,25-diol sapogenins (2a/2b, 5a/5b) for the tertiary 25-OH, mono 3-O-glucosyl ocotillol-PPD, 6-O-glucosyl ocotillol-PPT, 25-O-glucosyl ocotillol-PPD/PPT and 3,25-di-O-glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 66 publications
0
6
0
4
Order By: Relevance
“…同样, 在以 TMSOTf 为 促进剂的反应中, 反应温度的提高和溶剂极性的增加, 均使反应副产物增多(Entries 10~11). 再次, 我们探讨 了 Au(I)催化的糖基邻炔基苯甲酸酯型给体法 [15] , 以 Ph 3 PAuNTf 2 为催化剂, 转化率达到了 92%, 然而几乎无 目标产物 5a 获得(Entry 13), 说明本反应条件对 C-3 位 糖苷化没有选择性, 文献亦有类似报道 [7] . 最后, 我们 探讨了全乙酰基保护的糖基供体(donor)对 C-3 位糖苷化 选择性反应的影响, 对比全苯甲酰基保护糖基供体的糖 苷化反应(Entry 6), C-3 位糖苷化产物 5b 的产率明显降 低(Entry 14), 文献亦有类似无选择性的报道 [10e] .…”
Section: 结果与讨论unclassified
See 3 more Smart Citations
“…同样, 在以 TMSOTf 为 促进剂的反应中, 反应温度的提高和溶剂极性的增加, 均使反应副产物增多(Entries 10~11). 再次, 我们探讨 了 Au(I)催化的糖基邻炔基苯甲酸酯型给体法 [15] , 以 Ph 3 PAuNTf 2 为催化剂, 转化率达到了 92%, 然而几乎无 目标产物 5a 获得(Entry 13), 说明本反应条件对 C-3 位 糖苷化没有选择性, 文献亦有类似报道 [7] . 最后, 我们 探讨了全乙酰基保护的糖基供体(donor)对 C-3 位糖苷化 选择性反应的影响, 对比全苯甲酰基保护糖基供体的糖 苷化反应(Entry 6), C-3 位糖苷化产物 5b 的产率明显降 低(Entry 14), 文献亦有类似无选择性的报道 [10e] .…”
Section: 结果与讨论unclassified
“…因此, 有课题组研究了 PHQ 的 合 成 方 法 , 主 要 包 括 : (1) 俞 飙 课 题 组 [7] 报 道 了 以 20(S)-PPD 为原料, 先差异化保护 C-12 位和 C-3 位的羟 基, 再氧化环化, 并通过 C-3 位羟基脱保护分离出 C-24 位差向异构体, 然后再依次 C-3 位和 C-25 位羟基差异化 保护后, C-3 位羟基选择性脱保护, 用 Ph 3 PAuNTf 2 促进 剂与邻炔基苯甲酸酯型糖基供体糖苷化, 最后脱保护所 有羟基合成 PHQ 的线路, 总收率仅有 28.2%, 且促进剂 Ph 3 PAuNTf 2 的成本较高, 以及邻炔基苯甲酸酯型糖基 供体的制备较为复杂(Scheme 1, 线路 A); (2)李平亚课 题组 [6] 和 Yang 等 [5] 分别报道了以原人参二醇组皂苷和 Rh2 为原料, 经氧化环化合成 PHQ 的线路, 由 Rh2 合成 PHQ 的已知最高产率为 54.6% [4] , 但 Rh2 本身也是难得 的天然产物资源, 其化学合成从原料 20(S)-PPD 开始, 需要 C-12 位羟基先保护再糖苷化, 然后脱保护制得 [8] , 产率约在 47.4% [9] , 因此本线路的总产率也仅有 25.9% (Scheme 1, 线路 B). 图式 1 已报道的拟人参皂苷 HQ 合成方法 Scheme 1 Reported approaches for the synthesis of pseudoginsenoside HQ 和 C-25 位的羟基后才能有效地 C-3 位糖苷化 [7,8] , 增加 了反应步骤, 合成效率也因此低下. 且在奥克梯隆型皂 苷元上直接糖苷化探索研究中, 目前的糖苷化条件对 C-3 位糖苷化无选择性 [7,10] .…”
unclassified
See 2 more Smart Citations
“…The discovery of this type showed that the natural ones were mainly existed in American ginseng, Vietnam ginseng, or Panax japonicas [ 10 , 11 , 12 ]. Recently, the semisynthesis has been receiving more and more attention aiming to increase the yields or obtain the novel ocotillol-type saponin [ 13 , 14 , 15 , 16 ]. In our study, a novel ocotillol-type ginsenoside, named 12-riboside-pseudoginsengenin DQ (RPDQ), was semi-synthesized successfully by glycosylation reaction of pseudoginsengenin DQ.…”
Section: Introductionmentioning
confidence: 99%